The mechanism controling accounting risks in agrarian forming - O. N. Kuznetsova; A. E. Melguy; N. N. Kovalyova; Yu. A. Dvoretskaya (Аграрная наука Евро-Северо-Востока)
The Russian agrarian enterprises are need in improvement of financial positions. This problem can be solved if to increase the level of their economic safety. A policy of management of accounting risks may be the major tool which comes to light in accounting and analytical systems of many entities of the agrarian sphere. The research purpose is a development of optimum management mechanism of risks accounting in agrarian forming which will allow to minimize financial threats in the conditions of economic instability. Authors conducted a survey research of 36 agrarian forming of the Bryansk region (small, average and large). They revealed, compared and analysed the reasons of accounting risks of these entities. Unauthenticity of accounting information because of errors in the organization of financial accounting of agrarian forming is a typical factor of accounting risks (38.9 %). Unauthenticity of accounting information because of the average level of qualification of accountants occupies significant specific weight among the reasons of accounting risks (27.8 %) too. Insufficient competence of accountants in 8 surveyed agrarian forming applying the preferential mode on payment of a unified agricultural tax (single agricultural tax) when accounting transactions on a case of a bird led in 2016 to omission of an economic benefit in the amount of 54 360 rubles (6 795 rubles - on average, on each entity). More than 22 % of the agrarian entities are unprofitable; more than 61% of agrarian firms depend on external financing. As a result, authors offered the mechanism for minimization accounting risk for the entities of agrarian sector by internal and external factors. The central place is allocated to accounting consulting and outsourcing (especially for subjects of small agrarian business) in case of elimination of the accounting risks caused by external factors. If to minimize the accounting risks caused by external factors, then a key role is played by creation of an effective internal control system, and for average and large agrarian forming an important role is played by implementation of the high-quality system of management providing communication of the central office with remote divisions. Use of this mechanism in accounting and analytical practice of agrarian forming will increase the level of their economic safety, will improve a financial condition.